Study of Genetic Diversity of Aromatic Rice Genotypes Using Random Amplified Polymorphic DNA Markers (Journal of the Bangladesh Agricultural University, 2024)
The study of genetic variation in aromatic rice is necessary for enhancing and preserving its genetic makeup. In this study, we amplified four Random Amplified Polymorphic DNA (RAPD) markers from the genomes of 11 different aromatic rice genotypes in order to evaluate the genetic variation and relatedness in aromatic rice. The genotypes were collected from different sources- five of which were obtained from the Bangladesh Rice Research Institute, one from the Bangladesh Institute of Nuclear Agriculture, and the remaining five were local genotypes. In RAPD profiling, twenty-seven of the thirty-six bands that were generated by the four primers were polymorphic, resulting in an estimated average polymorphism of 47.22 percent. The average value of the polymorphic information content was 0.309 with a range from 0.165 to 0.456, indicating that the primers were effective to detect genetic diversity between the genotypes. The genetic diversity and Shannon information index across all of the genotypes and primers were 0.176 and 0.260, respectively, which indicated that there was a certain amount of genetic variation in the studied aromatic rice genotypes. Kalizira and Binadhan-9 genotypes had the smallest genetic distance (0.057), while it was the highest (0.406) between the BRRI dhan 34 and BRRI dhan 50. The genotype pairs BRRI dhan 38 vs BRRI dhan 34, BRRI dhan 38 and Kalizira, and Zirakatari and Kalizira had also a higher level (0.365) of genetic distances. The genotypes were grouped into two main clusters in the UPGMA dendrogram. Cluster I included five genotypes: BRRI dhan 34, Basmoti, Atashail, Kalizira, and Binadhan-9. Cluster II included remaining six genotypes: BR5, BRRI dhan 38, BRRI dhan 50, Uknimodhu, BRRI dhan 37, and Zirakatari. Documentation of the genetic variation and relatedness among the aromatic rice genotypes under this investigation could be useful for future research into the development of aromatic rice and related fields.J Bangladesh Agril Univ 22(3): 277-284, 2024